"Who am I? Who are we?" Understanding the impact of family business identity on the development of individual and family identity in business families. Issue 1 (March 2019) - Wielsma, Albertha J.; Brunninge, Olof
Highlights: The family business identity can affect the family identity and the individual identity development of family members. This impact is manifested in both professional and personal choices of family members. The impact of the firm identity can lead to loss of the family harmony. The impact of the firm identity can be explained by the strive for congruence between identity features. Developments in the identity of the owning family in turn impact the identity of the firm. Abstract: Family firms incorporate two identities, namely the identity of the firm and the identity of the family. Previous literature assumes that the owning family influences the identity of the firm by transferring the values and beliefs of the owners to the firm. However, identity theory suggests that identity formation is a dynamic process, based on iterations with the environment and interpretations of the past identity. In family firms this means that identity of the family can also be influenced by the firm. In this longitudinal study of a multi-generational family firm, we draw from identity literature to explore how the interplay between the business and the family identity can take place in a family firm. Our observations suggest that the identity of the firm can influence identity processes on various levels and that this is not necessarily beneficial for the family. Our study thus contributes to the understanding of identity issues in family firms.